New Method of Materials Flow Calculation for Double-String SLCI Type Cement Plant (Part 2: Suspension Preheater and Calciners) - Prihadi Setyo Darmanto; Izzan Hakim Muzakki; I Made Astina; Firman Bagja Juangsa; Alfi Amalia; Arief Syahlan (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
In many industries, energy auditing is important as the basis for controlling processes and designing additional equipment or modifying an existing plant. However, it requires detailed data of the materials flow, which often cannot be determined easily by direct measurement due to high-temperature limitations. This paper presents the second part of an integrated study to perform energy auditing in a separate line and in-line calciners (SLC-I) type cement plant. The second part of this study, as presented in this paper, focused on the materials flow calculation for eight separate cyclones and two calciners. The least square method was employed for solving the obtained overdetermined system equations. Using the operation data from Part 1 of the study, calculation of the detailed materials flow in each cyclone was executed. The results showed that the separation efficiency of cyclones 1A, 2A, 3A, 4A and 1B, 2B, 3B, 4B was 93.86%, 89.80%, 84.41%, 81.98% and 93.96%, 88.70%, 88.53%, 80.72% respectively and the estimated calcination percentage of kiln feed coming out of the ILC and the SLC was 85.3% and 56.3%, respectively. These values are impossible to be measured directly in the cyclones and calciners during plant operation.